Memorandum of Understanding between the Department of Environment, Earth and Resources, University of Manitoba and Institute of Governance Studies, BRAC University (2007) - Department of Environment, Earth and Resources, University of Manitoba; Institute of Governance Studies, BRAC University (Department of Environment, Earth and Resources, University of Manitoba and Institute of Governance Studies, BRAC University, 2013)
This Memorandum of understanding is effective from the 1st of August, 2007 between the University of Manitoba, on behalf of its Clayton H. Riddell, Faculty of the Environment, Earth and Resources and on behalf of the Institute of Governance Studies, BRAC University.